Modalities of Conjunctural Analysis: “Seeing the Present Differently” through Global Lenses - Hart, Gillian (Antipode, 2024)
The sub‐title of this essay refers to Antonio Gramsci's concept of “prevision”—understood as neither foresight nor prediction, but a method of political work that enables intervention in the present in order to change it. Prevision forms part of conjunctural analysis, which remains powerfully salient and urgent in our own time. Over the past decade attention to conjunctural analysis has surged across a number of disciplines. Yet some distinctly different modalities of conjunctural analysis are at play in this burgeoning work. The first two sections of this essay offer close readings of the conjunctural analyses of Gramsci and Stuart Hall; their respective relationships to the work of Louis Althusser; and the political work that conjunctural analysis was doing for each of them in relation to fascism and Thatcherism. Building on but moving beyond these analyses, the third section focuses on what it might mean to “globalise” conjunctural analysis in relation to the urgent challenges of the current conjuncture, in a way that sheds light on articulations of racist, gendered, sexualised, and other exclusionary and oppressive forms of difference in relation to class and capitalism.